Rational Use of Antibiotics in Childhood Pneumonia: A review - Mridha, Md Al Amin; Rahman, Md Shakibur (Bangladesh Journal of Child Health, 2024)
Inappropriate antibiotic treatment in childhood pneumonia may lead to greater expense, antibiotic resistance, toxic side effects, or even death. Important risk factors are infant and young children, low birth weight, nonexclusive breastfeeding, malnutrition, vitamin A deficiency, incomplete immunization and exposure to polluted air. Common organisms involved in pneumonia in neonatal periods are gram negative rods, group B streptococcus and staphylococcus. Beyond the neonatal period S. pneumoniae, H. influenzae, staphylococcus and mycoplasma are common. MRSA, gram negative rods and Legionella spp are commonly involved in nosocomial pneumonia. Rational use of antibiotic for bacterial pneumonia is based on probable organism, age, vaccination and clinical status of the child. Children who do not require hospitalization should have high doses of amoxicillin 90 mg/kg/day orally divided twice daily, alternatives include cefuroxime and amoxicillin/clavulanate. For schoolaged children when mycoplasma is suspected, azithromycin is generally preferred, alternatives clarithromycin can be given. Fully immunized against H. influenzae type b and S. pneumoniae children who are not severely ill should give ampicillin or penicillin G. For children who do not meet these criteria: ceftriaxone or cefotaxime should be given. If clinical features suggest staphylococcal pneumonia (pneumatocele or empyema), then include oxacillin or vancomycin. Vancomycin and meropenem are the initial treatment of choice for nosocomial pneumonia. Pneumonia in neonatal period should have ampicillin plus gentamicin or ceftazidime plus amikacin. Antibiotics should be continued until the patient has been afebrile for 72 hours, and the total duration should be 10 days. Selection of appropriate antibiotic in childhood pneumonia considering age of the child, risk factor, probable organism, immunization status and clinical severity are paramount important. BANGLADESH J CHILD HEALTH 2022; VOL 46 (3) : 102-109